Well-being trajectories and dynamic resource shifts in the transitions of retirement: a longitudinal study of Taiwanese older adults - Wan-Chen Hsu; Nuan-Ching Huang; Nuan-Ching Huang; Susan C. Hu (Frontiers in Psychology, 2025)
BackgroundPrevious literature highlights the heterogeneity of retirement adjustment, emphasizing various life experiences among retirees. The Dynamic Resource-Based Model provides an integrated framework to examine these differences, linking retirement adjustment to subjective well-being. This study applied the framework to Taiwan’s unique sociocultural context, in which distinct cultural values and retirement policies may create different adaptation patterns from those observed in Western societies. Thus, the main purposes of the study are to examine the heterogeneity in subjective well-being trajectories among Taiwanese retirees and focus on how various resources influence these diverse adaptation patterns within this specific cultural environment.MethodThis study utilized six waves of datasets from the Taiwanese Longitudinal Study on Aging (TLSA) spanning from 1996 to 2015, with 1,329 valid participants aged 50 and above in the analysis. Retirement was defined as the initiation of pension receipt during the observation period. Subjective well-being was measured using a 10-item Life Satisfaction Index. We first employed a Latent Growth Mixture Model (LGMM) to identify distinct trajectories of subjective well-being. Then, we applied the generalized linear model (GLM) to examine how physical, financial, cognitive, emotional, and social resources influence these trajectories across the following three stages: pre-retirement, transition, and post-retirement.ResultsOur findings revealed two main trajectories of subjective well-being during retirement: a “High-Increase” group and a “Low-Decline” group. Compared with the “Low-Decline” group, individuals in the “High-Increase” group exhibited better health, stronger economic status, greater social participation, more family support, and higher educational attainment. In addition, older adults with fewer illnesses, healthier behaviors, and a spouse/partner were more likely to maintain a high-increased well-being trajectory during the transition to retirement. Our findings further showed the critical importance of volunteering in enhancing subjective well-being after retirement.DiscussionThis study highlights the importance of understanding distinct well-being trajectories and how resources differently influence retirement stages in Taiwan’s unique context. Policymakers should recognize this heterogeneity rather than implementing one-size-fits-all solutions. Given the crucial role of family support in early retirement and the growing importance of volunteering later, policies should strengthen family systems while expanding social participation opportunities.